Finite Element Modeling and Parametric Analysis of Concrete-Filled Steel Tube Stub Columns under Axial Compression - Paudel, Arun; Lamichhane, Kabin; Subedi, Arun; Paudel, Ashim; Khadka, Rabin; Baidhya, Sagar; Singh, Avimanyu Lal; Gauli, Garima (Tribhuvan University Journal, 2026)
Concrete-filled steel tube (CFST) columns are composite structural members that combine the compressive strength of concrete with the confinement and ductility provided by a steel tube. Owing to the passive confinement mechanism and nonlinear material interaction, accurate numerical modeling of CFST behavior especially with high-strength concrete and thin-walled steel tubes remains challenging. This study presents a refined three-dimensional finite element model to simulate the axial compressive behavior of CFST stub columns. The model is developed using the concrete damaged plasticity framework, incorporating strain hardening–softening behavior for confined concrete and modified material parameters to capture confinement effects more accurately. The proposed model was validated against experimental results from the literature and laboratory tests, showing close agreement in load–strain response, stiffness, ultimate load, ductility, and deformation pattern; in the laboratory comparison, the numerical and experimental responses matched closely up to about 130 kN. Following validation, parametric analyses were conducted to evaluate the influence of concrete grade, steel tube thickness, slenderness ratio, and binding bars on CFST axial compression performance. Increasing steel tube thickness from 1.5 mm to 5.5 mm significantly enhanced yield capacity, increasing it from approximately 1,550 kN to 2,600 kN for M20 concrete, 1,995 kN to 2,800 kN for M25 concrete, and 2,050 kN to 3,100 kN for M30 concrete. Concrete grade mainly improved initial stiffness and yield strength, while post-yield behavior was governed largely by steel confinement. For stub columns with L/D ratios from 1.81 to 10.91, the axial force–strain response remained nearly identical up to yield, indicating limited slenderness influence within the short-column range. Although binding bars increased initial stiffness, they reduced post-yield strength and ductility due to stress concentration effects. A comparative cost assessment also showed that a CFST column carrying 1,287 kN was about 16.8% cheaper than an equivalent RC column. The findings provide useful insight for the efficient modeling and practical design of CFST stub columns under axial compression.